(untitled) (Journal of Social Sciences Review, 2023)
Organizational efficiency and effectiveness depend upon the implementation of rules, regulations and policies devised by the organization. Basically, organizations follow ethics, prescribed by their various religion. Those Countries following Islam, mainly follow Islamic work ethics. Studying Islamic work ethics and their impact on several attitudes and behavior of employees need time. This study examines the impact of Islamic work ethics on organizational citizenship behavior and organizational commitment through the mediating mechanism of job satisfaction. During the process of data gathering, 294 questionnaires from public and private sector banks of Quetta City were collected. Among 294 respondents 223 male and 71 female respondents participated in the survey. Descriptive and inferential statistics were employed for data analysis and evaluation. Linear regression was used for hypothesis testing and Andrew F. Hayes Process Macro Four was utilized for studying the mediating effect. The findings of the study reveal that Islamic work ethics is positively and significantly related to organizational citizenship behavior and job satisfaction significantly mediates the relationship between Islamic work Ethics and organizational citizenship behavior.